2015
DOI: 10.1007/s00391-015-0912-1
|View full text |Cite
|
Sign up to set email alerts
|

Bedeutung von außerhäuslichen Aktivitäten, Nachbarschaft und Stadtteilidentifikation für das Wohlbefinden im Alter

Abstract: The findings underline the need for an age-differentiated understanding of person-environment interchange processes in later life and in particular the importance of the neighborhood in very old age in this respect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0
11

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 16 publications
2
5
0
11
Order By: Relevance
“…Nevertheless, as already outlined in Penger & Oswald (2017), a mobility-related preference for routines was considerably more common in older participants. Because ROU is assumed to be associated with aspects of belonging in old age, this finding agrees with previous gerontological research indicating that personenvironment exchange processes (e.g., routines and habits), formed over many years, become more prominent when aging in place (e.g., Bouisson, 2002;Chaudhury & Oswald, 2019;Oswald & Konopik, 2015;Oswald et al, 2011;Penger et al 2019;Rowles & Bernard, 2013). Thus, ROU may have shown stronger associations when outcomes were linked to urban-related identity in the individual's immediate neighborhood.…”
Section: Discussionsupporting
confidence: 90%
“…Nevertheless, as already outlined in Penger & Oswald (2017), a mobility-related preference for routines was considerably more common in older participants. Because ROU is assumed to be associated with aspects of belonging in old age, this finding agrees with previous gerontological research indicating that personenvironment exchange processes (e.g., routines and habits), formed over many years, become more prominent when aging in place (e.g., Bouisson, 2002;Chaudhury & Oswald, 2019;Oswald & Konopik, 2015;Oswald et al, 2011;Penger et al 2019;Rowles & Bernard, 2013). Thus, ROU may have shown stronger associations when outcomes were linked to urban-related identity in the individual's immediate neighborhood.…”
Section: Discussionsupporting
confidence: 90%
“…Für die wachsende Zahl von Singlehaushalten im Alter stellen zentrale Ausstattungsmerkmale, wie Barrierefreiheit oder gute Verkehrsanbindung, wichtige Einflussgrößen dar, die eine Wohnung alten-und bedarfsgerecht machen. Im Wohnumfeld geht es v. a. um Faktoren, die das Erleben von biografischer Kontinuität ermöglichen, sowie um Gelegenheiten und Rahmenbedingungen zu Aufbau und Erhalt sozialer Beziehungen [8].…”
Section: Strukturelle Rahmenbedingungen Für Neue Wohnund Pflegearrangunclassified
“…Furthermore, in a study by Naumann (2006), older people reported on "knowing what is going on in the neighbourhood" (p. 196). Oswald and Konopik (2015) found that such "knowings" -which are not detectable by camera pictures -are relevant to individuals' well-being, especially in older age. Another point to consider is the given study design, which does not provide information about causality between out-of-home mobility and social participation.…”
Section: Discussionmentioning
confidence: 94%
“…However, getting older is not associated with negative changes per se. Being physically active and out-of-home mobility promote people's health (Faß and Schlesinger 2019), autonomy, identity and well-being, even in older age (Claßen et al 2014;Hamer et al 2014;Oswald and Konopik 2015;Wahl et al 2012). Active engagement, which includes active social participation and (active) mobility (Rowe and Kahn 1997), is an essential component of ageing well (Wahl et al 2012), reduces premature mortality (Maier and Klumb 2005;Pynnönen et al 2014;Thomas 2012) and morbidity (Hwang Han et al 2017) and increases cognitive function (Miceli et al 2018) and well-being (Bauman et al 2016).…”
Section: Introductionmentioning
confidence: 99%